Soviet Politburo Decisions and the Emergence of the North Korean State, 1946-1948 - Andrei Lankov (Korea observer, 2005)
The article analyzes the decisions of the Soviet Politburo related to the Korean issues and approved in 1945-1948. The set of the documents is new, and with exception of few documents have never been studied before. The research indicates that from at least summer 1946 the Soviet side perceived the divi-sion of country as inevitable. The research also indi-cates that the Soviet role in the North Korean deci-sion-making was paramount. It is clear that all major political decisions made by Pyongyang in 1948 had been approved by Moscow beforehand. The major declarations, including the North Korean Constitu-tion, also received the formal approval of the Soviet government. The newly available documents demon-strate that the North Korean and Soviet side did not expect a unified Korean state to emerge, and worked towards strengthening the Pyongyang rule in the Northern part of the country. KCI Citation Count: 1